(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
As tidal turbines are operated for longer periods, the effects of frequent and large-scale fluctuations in hydrodynamic loading are of significant importance. These fluctuations in hydrodynamic loading can lead to fatigue damage of turbine blades, particularly for floating turbines operating in shallow water conditions when influenced by waves. Thus, the fatigue loading on tidal turbines must be accurately evaluated within the design stage to ensure the long-term durability and longevity of these devices. To investigate the hydrodynamic performance of tidal turbines under ocean flow conditions and evaluate the resultant fatigue loadings, a three-dimensional computational fluid dynamics (CFD) model of a horizontal axis tidal turbine rotor has been developed using ANSYS CFX. The hydrodynamic forces predicted by the CFD model under tidal current conditions are compared to the forces observed during the experimental trials on the prototype turbine. In addition, a numerical wave tank model has been developed to investigate the hydrodynamic performance of this tidal turbine model when influenced by different current and wave conditions, in which, the water velocities inlet method has been adopted and the wave parameters are calibrated from the physical wave tank measured data. Then, in this study, the physical tidal turbine model is 3D printed and is used to conduct a series of hydrodynamic tests in the physical wave tank, where the hydrodynamic loadings on the turbine and the blockage effect at different depths to still water level (SWL) under various wave conditions have been systematically investigated. The results show that under wave loadings, the variation amplitude of the thrust force on the model turbine decreases with the increase of the depth to SWL and increases with the decrease of the wave period from 1.67 s to 0.93 s. Twin turbine tests have also been conducted, from which the results reveal that the twin turbine can experience 1.25 to 2 times the hydrodynamic loadings on a single turbine, and the thrust can be increased by increasing the bending angle due to the cluster interactions. This research evaluates the fatigue loadings on tidal turbines under wave conditions, which can help improve the present fatigue design and support the development of tidal energy. In the long run, this research can help society achieve sustainable development goals and reach ‘net zero’ CO2 emissions by 2050.